KELAYAKAN TEKNO-EKONOMI MIGRASI TEKNOLOGI PROSES PRODUKSI GULA KRISTAL PUTIH DARI SULFITASI KE DEFEKASI REMELT KARBONATASI - Subiyanto, Subiyanto (Badan Pengkajian dan Penerapan Teknologi, 2012)
Sugar is a strategic commodity for Indonesia, such that the availibility and the price have been managed by the government. The national production of Indonesia sugar has not been enough to cover the consumption, such that the deficit must be imported. Indonesian sugar was produced by 61 factories, where 51 units are State-owned Company. Unfortunately, the quality of sugar produced by State – owned factory has been getting worse, such that some are not qualified to the Indonesian National Standards (SNI). One of the reasons is poor process technology adopted, which is mostly using sulfitation technology. The Government, therefore, encourages industry to migrate the process technology from sulfitationsystem to defecation remelt carbonatation (DRK) system. This study assesses the techno-economy feasibility of the migration. The results indicate that technology migration is technically feasible, but for the business, Government needs to give price incentive to the product. Furthermore, the study recommends that adoption of DRK technology should be prioritized to the factories with abundant stock of baggase.